2016
DOI: 10.1097/aog.0000000000001673
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin and Aspirin Compared With Aspirin Alone to Prevent Placenta-Mediated Pregnancy Complications

Abstract: ClinicalTrials.gov, https://clinicaltrials.gov, NCT00986765.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 30 publications
0
79
0
4
Order By: Relevance
“…44 It is reassuring that the number of bleeding events in the antepartum and postpartum periods is comparable or lower with the total bleeding rates reported in randomized trials evaluating prophylactic LMWH and ASA during pregnancy or in the postpartum period in women without ET. [45][46][47][48] It is further reassurance that there was no antepartum bleeding reported in women with ET who received a combination of ASA and LMWH during their pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 It is reassuring that the number of bleeding events in the antepartum and postpartum periods is comparable or lower with the total bleeding rates reported in randomized trials evaluating prophylactic LMWH and ASA during pregnancy or in the postpartum period in women without ET. [45][46][47][48] It is further reassurance that there was no antepartum bleeding reported in women with ET who received a combination of ASA and LMWH during their pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies or a meta-analysis is still needed to better quantify the risk, if any, of placenta-mediated pregnancy complications in women with ET, including what role ASA, LMWH, or IFN has in preventing pregnancy loss or placenta-mediated complications. In the non-ET population, recent data from randomized controlled trials and an individual patient-level meta-analysis of 963 pregnant women in 8 trials found that there is no role for antepartum ASA or LMWH prophylaxis in preventing pregnancy loss or placenta-mediated pregnancy complications, including those with inherited thrombophilia, 48,[56][57][58][59][60] with the exception of ASA and preeclampsia. 60 Further research evaluating the role of LMWH for the subgroup of women with past placenta abruption is still needed.…”
Section: Discussionmentioning
confidence: 99%
“…27 More recent studies have examined the effect of prophylactic anticoagulation in addition to aspirin on placenta-mediated complications with conflicting results. 2830 The evidence regarding the dose-dependent efficacy and impact of gestational age at initiation are similarly poorly defined. 31, 32 …”
Section: Commentmentioning
confidence: 99%
“…Most recently, the large, well-designed HEPEPE and EPPI trials reported that enoxaparin with ASA does not significantly reduce placental-mediated complications, including preeclampsia, when compared to aspirin alone [31,32]. The conclusions of systematic reviews and meta-analyses summarizing this literature are conflicting.…”
Section: Lmwh For Preeclampsia Prevention: Evidence From Clinical Trialsmentioning
confidence: 84%
“…The criteria utilized to identify women as 'high risk' of developing preeclampsia have thus far differed greatly between trials. The majority of trials utilized inclusion criteria of prior preeclampsia, placental-mediated complication or pregnancy loss to identify women who are considered at high risk of preeclampsia in the current pregnancy; this was the approach in the recent HEPEPE and EPPI trials [31,32]. The primary outcome of these clinical trials has typically consisted of a composite clinical outcome, including preeclampsia, small for gestational age, placental abruption, and maternal or perinatal death.…”
Section: Patient Selectionmentioning
confidence: 99%